Growth of AlN, GaN and InN from the solution. (1st December 2004) - Krukowski, S.; Grzegory, I.; Bockowski, M.; Lucznik, B.; Suski, T.; Nowak, G.; Borysiuk, J.; Wroblewski, M.; Leszczynski, M.; Perlin, P.; Porowski, S.; Weyher, J.L.
Thermodynamic and kinetic properties of group III metal nitrides Me(Al, Ga, In)N-Me(l)-N2 systems are strongly influenced by the high binding energy of molecular nitrogen which favours the decomposition of these compounds into the constituents, severely limiting the growth possibilities of these crystals. From all three nitrides, the AlN sizeable crystals have been grown from the vapour only. In contrast, the best GaN and InN crystals were grown from solution using different nitrogen sources: ammonia (NH3 ), plasma-activated nitrogen, or molecular nitrogen (N2 ) under high pressure. AlN crystals grown from solution have low crystallographic quality and needle-like unstable morphology. They are electrical insulators. GaN hexagonal plate-like crystals, grown under high nitrogen pressure, have high crystallographic quality, sufficient for epitaxy. GaN undoped crystals, are heavily n-type whereas those doped by Mg or Be are usually semi-insulating. InN crystals, obtained by the plasma method, are similar to undoped GaN crystals - they possess high concentration of free electrons.